2016
DOI: 10.1111/jfpp.12815
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Edible Coating Techniques on Quality Characteristics of Eggs

Abstract: The core objective of current research work is to observe the effects of different edible coatings on eggs for enhancing shelf life. For the purpose, brown and white eggs were procured from different local farms. After application of edible coatings i.e. shellac and chitosan, the quality characteristics i.e. haugh unit, yolk index, yolk color, albumin pH and shell color were observed. The maximum yolk index occur in noncoated eggs that is 0.42 for desi and 0.43 for farmi to 0.26 for desi and 0.23 for farmi whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
2
7
0
4
Order By: Relevance
“…In line with the results of the present study, Saeed et al. (2017) reported that b * values of the yolk of egg samples decreased during storage and coating slowed down this decrease.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In line with the results of the present study, Saeed et al. (2017) reported that b * values of the yolk of egg samples decreased during storage and coating slowed down this decrease.…”
Section: Resultssupporting
confidence: 93%
“…The highest b* values in the albumen and yolk (5.29 and 15.21, respectively) during storage were determined in the samples stored at 22 • C after washing whereas the lowest b* values in the albumen and yolk (7.39 and 23.41, respectively) were determined in the samples coated with sour cherry tree resin. In line with the results of the present study, Saeed et al (2017) reported that b* values of the yolk of egg samples decreased during storage and coating slowed down this decrease.…”
Section: F I G U R Esupporting
confidence: 93%
See 3 more Smart Citations